Cabellos y barbas: narrativas de hombres de clase media alta limeña - Kogan, Liuba (2021)
In this paper we explore the hair and beard grooming narratives of fourteen upper-middle-class men aged between 27 and 40 years from Lima, as well as those of barbers and barbershop managers. We conduct in-depth interviews and analyze their thematic and interpretive content, questioning to what extent the focus on male appearance elucidates gender, race and class relations. We find that the interviewees use various strategies to avoid being feminized by their interest in grooming. At the same time, the subjects seek to match their hairstyle and/or beard with their clothing and body type in order to appear well turned-out; in Peru, this practice is strongly linked to racial, gender and class narratives.